Tata Kelola Kelembagaan Pedagang Kaki Lima Sekitar Pasar Di Kota Kendari - Habri Jaya; Marsuki Iswandi; La Ode Alwi (Jurnal Perencanaan Wilayah, 2021)
The condition of street vendors in Kendari City is currently not as crowded as cities in other provinces, but the trend of the number of street vendors is increasing every year. This can be seen from the decreasing function of the sidewalk for pedestrians because it is used by street vendors to carry out their activities. The purpose of this study is to determine the characteristics of street vendors and the factors of the presence of street vendors who occupy the sidewalks and shoulders of the road in Kendari City. The method used to analyze the factors of the presence of street vendors who occupy the shoulders and sidewalks and to determine the control system for street vendors who use the shoulders and sidewalks uses descriptive analysis. The results of this study are the characteristics of street vendors (PKL): main occupation (87%), types of vegetables into merchandise (14%), duration of trade <5 years (69%), and area of 2-4 m2 (80%) The factors for the existence of street vendors (PKL) occupying the shoulders and sidewalks around the market in Kendari City are weak rule enforcement, transactional systems, no place in the market, and location costs. Keywords: Governance, Street Vendors, Market Kondisi pedagang kaki lima di Kota Kendari saat ini belum sepadat kota-kota di Provinsi lain, namun kecenderungan jumlah PKL setiap tahunnya mengalami peningkatan. Hal ini dapat dilihat dari semakin berkurangnya fungsi trotoar jalan bagi pejala kaki karena digunakan oleh pedagang kaki lima untuk melakukan kegiatannya. Tujuan dari penelitian ini yaitu untuk mengetahui karakteristik pedagang kaki lima dan faktor-faktor keberadaan pedagang kaki lima yang menempati trotoar dan bahu jalan di Kota Kendari. Metode yang digunakan untuk menganalisis faktor-faktor keberadaan pedagang kaki lima yang menempati bahu jalan dan trotoar serta untuk mengetahui sistem penertiban pedagang kaki lima yang menggunakan bahu jalan dan trotoar menggunakan analisis deskriptif. Hasil penelitian ini yaitu karakteristik pedagang kaki lima (PKL): pekerjaan utama (87%), jenis sayuran menjadi barang dagangan (14%), lama berdagang <5 tahun (69%), dan luas tempat 2-4 m2 (80%).Faktor-faktor keberadaan pedagang kaki lima (PKL) menempati bahu jalan dan trotoar disekitar pasar di Kota Kendari adalah lemahnya penegakan aturan, sistem transaksional, tidak ada tempat di dalam pasar, dan biaya lokasi..Kata Kunci: Tata Kelola, Pedagang Kaki Lima, Pasar